Antidiarrheal, antioxidant and antimicrobial activities of the musa sapientum seed - Hossain, M Sarowar; Alam, M Badrul; Asadujjaman, M; Zahan, Ronok; Islam, M Monirul; Mazumder, M Ehsanul H; Haque, Md Ekramul (© 2011, Avicenna Journal of Medical Biotechnology., 2016)
This article was published in Avicenna Journal of Medical Biotechnology [© 2011, Avicenna Journal of Medical Biotechnology] and the definite version is available at: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC3558179/